High corrosion resistance of twin boundaries in medium-entropy alloy exposed to liquid lead-bismuth eutectic at 500 °C: Mechanism exploration by both experiment and first-principles calculation. (February 2023) - Hu, Yanying; Niu, Yitian; Chen, Jinhong; Zhou, Hang; Zhou, Pujun; Ma, Xianfeng; Wang, Da; Liu, Wenguan; Gong, Xing
Abstract: The present study discovered the twin boundaries (TBs) of CoCrNi medium-entropy alloy (MEA) exhibited high corrosion resistance to liquid lead-bismuth eutectic (LBE) at 500 °C with 5 × 10 −7 mass% dissolved oxygen. The grain boundaries (GBs) were corroded by LBE, forming brittle Bi3 Ni phases in LBE interior and at the LBE/CoCrNi interface. First-principles calculation indicated that the Bi diffusion energy barriers at GBs and TBs were 0.69 eV and 1.52 eV, respectively. The high diffusion barrier for Bi atom in CoCrNi MEA contributed to the high corrosion resistance of TBs in the liquid LBE. Highlights: This is the first report to estimate the corrosion behavior of medium-entropy alloy in liquid lead-bismuth eutectic (LBE). The twin boundaries (TBs) show excellent resistance to the LBE attack. The Bi diffusion energy barriers at grain boundaries (GBs) and TBs are 0.69 eV and 1.52 eV, respectively. The high diffusion barrier for Bi atom in CoCrNi contributes to the high corrosion resistance of TBs in the liquid LBE.